The ameliorative effects of Nigella sativa, thymoquinone, and bentonite against aflatoxicosis in broilers via AFAR and Nrf2 signalling pathways, and down-regulation of caspase-3 - Ates, M. B.; Ortatatli, M.; Oguz, H.; Ozdemir, O.; Terzi, F.; Ciftci, M. K.; Hatipoglu, F. (Informa UK Limited, 2021)
1. Aflatoxins (AFs) are metabolites which especially have toxic effects on proteins, and are detoxified by the aflatoxin-B1 aldehyde reductase (AFAR) pathway. In this pathway, the aldo-keto reductase family 7, member A2 (AKR7A2) enzyme, which is controlled by nucleic-related erythroid factor 2 (Nrf2), plays an active role. However, data on the efficacy of this critical pathway in broilers is limited. 2. The aim of the following study was to investigate the changes in the expression levels of AKR7A2, Nrf2, and caspase-3, and the effects of Nigella sativa seeds (NS), thymoquinone (TMQ), and bentonite (BNT) in broilers exposed to AFs. 3. One-hundred broilers were divided into ten groups (control (CNT); AF; NS; TMQ; BNT; AF+TMQ; AF+NS; AF+BNT; AF+BNT+NS; AF+BNT+TMQ) and fed for 28 d. AF, TMQ, NS and BNT were added to diets at levels of 2 mg/kg, 300 mg/kg, 50 g/kg and 10 g/kg respectively. 4. The addition of AF to the diet decreased AKR7A2 and Nrf2 levels dramatically, but increased caspase-3 (P < 0.01). TMQ, NS and BNT additions to the diet eliminated all negative effects caused by AF (P < 0.01); and AKR7A2 and Nrf2 were further raised in TMQ and NS groups when compared to the control group. TMQ and NS showed a positive effect on detoxification parameters when given together with BNT. 5. Supplementation with NS and TMQ enhanced AF detoxification via the AFAR pathway, by increasing AKR7A2 and Nrf2 levels, in addition to reducing hepatocyte apoptosis.
Keywords: Caspase 3; NF-E2-Related Factor 2; AKR7A2; apoptosis; black cumin; liver; Mycotoxin; Nrf2; Down-Regulation; Mycotoxicosis; Foodborne Diseases; Aflatoxins; Aldehyde Reductase; Bentonite; Benzoquinones; Animals; Nigella sativa; Chickens; 3. Good health